Ask a New Question
Search
Ben and Cole have 36
Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6x+7
Cole said that the vertex is (3, 2). Is Cole correct? If not,
1 answer
48 views
In "Touching Spirit Bear," the book, I have to answer these questions.
1. Why does Cole think the bear attacked him? 2. In what
1 answer
asked by
Alexis Herda
626 views
Cole rewrote a quadratic function in vertex form.
h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+_) +7 Step 2: h(x)= (x2−6x+ 9)+7 −9
3 answers
52 views
Cole rewrote a quadratic function in vertex form.
h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
3 answers
44 views
Cole rewrote a quadratic function in vertex form.
h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
1 answer
41 views
Cole rewrote a quadratic function in vertex form.
h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
5 answers
39 views
Cole rewrote a quadratic function in vertex form.
h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+ )+7 Step 2: h(x)=(x2−6x+ 9 )+7 −9
1 answer
60 views
Cole rewrote a quadratic function in vertex form.
h(x) = x²-6x+7 Step 1: h (x) = (x²-6x+)+7 Step 2: h (x) = (x²-6x+9)+7-9 Step
1 answer
63 views
Cole rewrote a quadratic function in vertex form.
h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+ 9 )+7 Step 2: h(x)=(x2−6x+ 9 )+7 −9
1 answer
133 views
Cole can use the fomrula c=3.99n to find the cost c of buing n notebooks . if Cole has $15 to spend, which is a reasonable range
1 answer
asked by
Jessie
486 views